2006
DOI: 10.1097/00024382-200610001-00044
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the Complement Function After Multiple Trauma in Humans

Abstract: After multiple trauma, development of systemic inflammatory response and innate immune dysfunction have been described, reflected by disturbances of the cellular defense and uncontrolled activation of the complement system. However, little is known about the complement function during the early posttraumatic period (< 90 min after accident). Therefore, we investigated the complement status and function in sera from trauma victims (n=40 with an injury severity score of ISS=35.2 „b 3.1), obtained at the scene, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Furthermore, the degree of complement activation and development of a "complementopathy" (Fig. 2) seems to be crucial for the subsequent inflammatory response and the outcome of polytraumatized patients [8]. This is in accord with other reports, which suggested the use of the C3a/C3 ratio for scoring severity and outcome of trauma [9].…”
Section: Trauma-induced Complementopathysupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, the degree of complement activation and development of a "complementopathy" (Fig. 2) seems to be crucial for the subsequent inflammatory response and the outcome of polytraumatized patients [8]. This is in accord with other reports, which suggested the use of the C3a/C3 ratio for scoring severity and outcome of trauma [9].…”
Section: Trauma-induced Complementopathysupporting
confidence: 86%
“…Our own studies have revealed that multiple injury is associated with extensive, uncontrolled activation of complement [8].…”
Section: Trauma-induced Complementopathymentioning
confidence: 99%
“…It was previously shown that the complement system was rapidly activated after injury in the rat model of blunt chest trauma and triggered several downstream effects of the systemic inflammation, such as cytokine release and increased neutrophil numbers, phagocytosis, chemotaxis and respiratory burst induction 7. Clinically, the complement system is also rapidly activated after initial trauma,1, 26 with complement anaphylatoxins shown to be correlated with injury severity and mortality 1, 5, 27, 28. We showed that C5a serum levels increased during the first 24 h after the initial trauma and returned to baseline values after 72 h, independently of an additional blunt chest trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases the activation pathways lead to the production of the important anaphylatoxin C5a 9, 10. In trauma victims, systemic C5a immediately increased within minutes and was strongly correlated with injury severity 11, 12. C5a induces for example the migration of phagocytes, degranulation of mast cells, systemic cytokine release, respiratory burst induction, and the regulation of apoptosis in inflammatory cells, thus acting at the very first line of defense in the posttraumatic systemic inflammatory response 1.…”
mentioning
confidence: 99%